2016
DOI: 10.1016/j.japh.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist prescription of hormonal contraception in Oregon: Baseline knowledge and interest in provision

Abstract: Objective Oregon has implemented legislation expanding the scope of pharmacists to directly prescribe short-acting hormonal contraception (pill and patch) without a medical prescription. Pharmacists are critical to the success of the new law, but relatively little is known about their intent to prescribe contraception, or the motivators or barriers in providing this service. Methods Cross-sectional survey of pharmacists practicing in Oregon prior to legislative implementation. We analyzed responses to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 19 publications
6
52
0
1
Order By: Relevance
“…Despite efforts to support this initiative, the low number of pharmacist-initiated prescriptions might reflect liability concerns with a new scope of practice, time limitations, and discomfort with discussing overdose risk with patients. 21 The steady increase in naloxone prescriptions per month correlates with increased provider trainings and EHR alerts. The similar proportion of intranasal and intramuscular naloxone prescribed might reflect providers' increased familiarity and trust with intramuscular naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to support this initiative, the low number of pharmacist-initiated prescriptions might reflect liability concerns with a new scope of practice, time limitations, and discomfort with discussing overdose risk with patients. 21 The steady increase in naloxone prescriptions per month correlates with increased provider trainings and EHR alerts. The similar proportion of intranasal and intramuscular naloxone prescribed might reflect providers' increased familiarity and trust with intramuscular naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…As pharmacists in more states are allowed to prescribe hormonal contraception, it is important to understand pharmacist perceptions on performing this patient care service. Previous studies have evaluated patient, 20 provider, 21 student pharmacist, 22 and pharmacist [23][24][25] attitudes toward pharmacist-initiated contraceptives, but there is a lack of research focused on pharmacist attitudes in states currently without implemented legislation. Furthermore, there is a lack of published research in the past 5 years when pharmacists in multiple states have already gained the authority to prescribe hormonal contraception.…”
Section: Discussionmentioning
confidence: 99%
“…In a crosssectional survey of Oregon pharmacists practicing before the legislative implementation, the 3 greatest barriers to pharmacist participation in prescribing hormonal contraception were shortage of pharmacy staff to provide services, concerns about liability, and a need for additional training. 23 In another study, pharmacists' comfort level and attitudes were assessed regarding providing pharmacy access to hormonal contraception, and the major barriers were lack of payment mechanisms for providing the services, liability issues, and constraints on pharmacist's time. The majority of pharmacists in that study were comfortable with performing various tasks involved in delivering pharmacy access to hormonal contraception, such as measuring blood pressure and weight, asking risk assessment questions about the patient's medical history, and educating on the proper use of selected method, but, similarly to this study, the majority of pharmacists surveyed also reported a need for additional training.…”
Section: Discussionmentioning
confidence: 99%
“…3,24 A 2015 survey of Oregon pharmacists showed that 57% were interested in prescribing contraceptives, but only 39% planned to participate. 25 Those practicing in urban settings and those currently providing emergency contraception were more likely to indicate they planned to prescribe. Patients who received a pharmacist-prescribed contraceptive from a supermarket-based pharmacy chain in Oregon and California between August 2016 and February 2017 had the following characteristics: health insurance (74%), seen a physician in the previous year (89%), and previously used hormonal contraceptives (91%).…”
Section: Methodsmentioning
confidence: 99%